2021
DOI: 10.1038/s41586-021-03863-y
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple hominin dispersals into Southwest Asia over the past 400,000 years

Abstract: Pleistocene hominin dispersals out of, and back into, Africa necessarily involved traversing the diverse and often challenging environments of Southwest Asia1–4. Archaeological and palaeontological records from the Levantine woodland zone document major biological and cultural shifts, such as alternating occupations by Homo sapiens and Neanderthals. However, Late Quaternary cultural, biological and environmental records from the vast arid zone that constitutes most of Southwest Asia remain scarce, limiting reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 35 publications
4
37
0
2
Order By: Relevance
“…2000 km. During MIS 5 this region had favorable hotspots that included lakes and permanent springs 14 , 19 which could have sustained hominin groups traveling between the two regions. Various field expeditions revealed dozens of find spots and surface sites in the Negev and Arabia bearing elements from both lithic traditions: the centripetal and the Nubian 15 18 , 21 , 41 , 49 , 50 , 68 – 72 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000 km. During MIS 5 this region had favorable hotspots that included lakes and permanent springs 14 , 19 which could have sustained hominin groups traveling between the two regions. Various field expeditions revealed dozens of find spots and surface sites in the Negev and Arabia bearing elements from both lithic traditions: the centripetal and the Nubian 15 18 , 21 , 41 , 49 , 50 , 68 – 72 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-disciplinary studies carried out over the last two decades have shown that this arid belt was subjected to several wet episodes, which narrowed its geographical boundaries 3 7 . The strongest and most recognized episode, evident in various records, occurred in MIS 5 (130–80 kya), which is the timespan associated with hominin and faunal expansions to south Arabia and the Levantine corridor 8 – 14 . During this phase, the Arabian desert sustained lakes and wetlands which attracted hominins, most likely from African origins, bearing Nubian Levallois core technology 15 19 .…”
Section: Introductionmentioning
confidence: 99%
“…1 – 3 ), particularly the eccentricity-modulated precessional cycle (Extended Data Fig. 1a ), further created multiple human migration corridors from sub-Saharan Africa into northern Africa, the Arabian Peninsula and Eurasia 7 10 . The existence of these corridors is well supported by fossil, archaeological 9 and genetic 11 evidence.…”
Section: Mainmentioning
confidence: 99%
“…These extreme increases in rainfall permitted the formation of large, deep and perennial lakes and other waterbodies in the now arid interiors (Rosenberg et al, 2011;Rosenberg et al, 2012;Petraglia et al, 2012;Rosenberg et al, 2013;Parton et al, 2013;Parton et al, 2015a). As well as increased surface water availability and refilling of aquifers, increased rainfall led to "greening" events of Arabia, in which grassland environments expanded into the now arid desert interiors and supported the spread of large mammals and human settlement (Rose et al, 2011;Petraglia et al, 2012;Groucutt et al, 2015;Stimpson et al, 2016;Groucutt et al, 2018;Stewart et al, 2020a;Stewart et al, 020b;Groucutt et al, 2021;Scerri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%